Class cleavages and ethnic conflict: Coptic Christian communities in modern Egyptian politics - Sedra, Paul (Islam and Christian-Muslim relations, 1999)
Whereas the political claims of Egyptian Islamists have attracted much attention in Western media and scholarly circles, only rarely have such circles acknowledged the role played by ethno‐religious consciousness among Coptic Christians in Egyptian political life. This article analyzes the development of this consciousness through the nineteenth and twentieth centuries, as well as the socio‐economic roots of ‘Coptist’ political action. Accorded particular attention is the emergence of an explicitly sectarian political discourse among groups of middle‐class Copts in the 1970s, and the related spread of ethnic consciousness through the Coptic community at large since that time.